Undefined Terms: Empires and Emperors in Late Medieval French Thought. (October 2017) - Jones, Chris
Between 1200 and 1350, the meaning attributed to the terms 'emperor' and 'empire' evolved in France to reflect the growth in power of the Capetian-Valois kings and a concomitant decline in the authority exercised by contemporary Romano-German rulers. Both terms were ubiquitous in France in this period. The fact that neither was adopted to describe the expansion of royal power was because, as this article will demonstrate, its growth was considered a consolidation of existing rights and was limited by deep-seated concerns for legitimacy, neither of which fostered imperial comparisons. At the same time, a multi-layered understanding of imperial terminology developed in France. On one level, 'empire' and 'emperor' became interchangeable with 'kingdom' and 'king'. Yet imperial vocabulary remained highly malleable. Philip IV's conflict with the papacy led to the development of specific arguments intended to undermine any subordination of French royal authority to external parties. However, far from becoming irrelevant, the terminology of empire became integral to contemporary French political discourse. It offered solutions to otherwise insoluble problems. The article establishes the way in which the office of emperor came to be understood as, simultaneously, a limited form of temporal kingship but one that encompassed a universal role disassociated from government. Imperial terms were transmuted in French thought from an association with the exercise of universal temporal authority to signify a specialised function. This function was usually, but not exclusively, understood as leadership of the crusade.